2020
DOI: 10.1021/acs.jced.0c00127
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Mathematical Correlation of Ticagrelor in Different Pure Solvents

Abstract: The solid–liquid phase equilibrium of ticagrelor in methanol, ethanol, n-propanol, isopropanol, 1-butanol, isobutanol, n-octanol, acetonitrile, ethyl acetate, toluene, 2-butanone, and cyclohexanone at the temperature range from 273.15 to 313.15 K was measured by using the isothermal dissolution equilibrium method under the pressure of 101.2 kPa. The solubility data were analyzed by high-performance liquid chromatography, and the results increased with the rising temperature. The maximum value was obtained in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The reason why 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one is dissolved in THF may be due to THF, and 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one has the same ring structure; moreover, the oxygen atom on the furan ring of THF has a lone pair of electrons, which will form a strong NH···O bond with the NH on the unsaturated ring of 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one to improve solubility. Both 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one and DMF have amide groups, which may be the reason for the dissolution in DMF. Isophorone, ethyl acetate, and the solute have the same carbonyl structure, which may be the reason for the solute dissolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one is dissolved in THF may be due to THF, and 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one has the same ring structure; moreover, the oxygen atom on the furan ring of THF has a lone pair of electrons, which will form a strong NH···O bond with the NH on the unsaturated ring of 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one to improve solubility. Both 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido­[2,3]­pyrimidin-7­(8 H )-one and DMF have amide groups, which may be the reason for the dissolution in DMF. Isophorone, ethyl acetate, and the solute have the same carbonyl structure, which may be the reason for the solute dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…x A is the mole fraction of THF in the binary solvent without the solute, with uncertainty u(x A ) = 0.005. h i b i t e d .of electrons, which will form a strong NH•••O bond with the NH on the unsaturated ring of 6-bromo-2-chloro-8-cyclopentyl-5-methylpyrido[2,3]pyrimidin-7(8H)-one to improve solubility. Both 6-bromo-2-chloro-8-cyclopentyl-5methylpyrido[2,3]pyrimidin-7(8H)-one and DMF have amide groups, which may be the reason14 for the dissolution in DMF. Isophorone, ethyl acetate, and the solute have the same carbonyl structure, which may be the reason for the solute dissolution.…”
mentioning
confidence: 99%
“…Chen et al have reported the solubility data of TCG in methanol, ethanol, n-propanol, isopropanol, n-butanol, ethyl acetate, 2-butanone, and cyclohexanone. 37 In this work, the solubility data of Form V TCG in the same eight solvents and of Form II TCG in n-propanol, isopropanol, n-butanol, and ethyl acetate have been measured. The comparison charts of solubility data are shown in Figures 14 and 15.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%
“…The λ h model (eq ) was proposed by Buchowski et al It is based on the solid–liquid equilibrium relationship, which can relate the solubility to temperature. It could reveal the relationship between the activity of a solvent under equilibrium conditions and the solubility data of a solute in a hydrogen bonding system. In eq , λ and h are two adjustable parameters, which are related to the associated number of solute molecules and the excess enthalpy of the solution. T m is the melting temperature (K) of AAKG. …”
Section: Solubility and Model Calculationsmentioning
confidence: 99%